Capital Requirements for Government Bonds - Implications for Financial Stability - André Sterzel; Ulrike Neyer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Banks hold relatively large amounts of government bonds. Large sovereign exposures reinforce possible financial contagion effects from sovereigns to banks and are a risk for financial stability. Using a theoretical model, we find that the introduction of capital requirements for government bonds induce banks to decrease their investment in government bonds and to increase their investment in high yield assets. This implies that banks' balance sheets become more resilient.
Keywords: G28; G21; G01; 330